Dampak Penggunaan Media Sosial Terhadap Perilaku Belajar Siswa - Dela Agustiah; Taty Fauzi; Erfan Ramadhani (Islamic Counseling : Jurnal Bimbingan dan Konseling Islam, 2020)
This research is based on the fact that there are still students who do not understand the use of social media properly so that it has an impact on student learning behavior at school. This has an effect on the unsatisfactory student learning outcomes at school because social media is not used for learning but is used more as a place of entertainment. Based on this, this study will reveal how the influence of the use of social media on learning behavior. The method used in this research is correlational quantitative data collection using a Likert scale. Then analyzed using the help of the SPSS 16.00 for windows program. The results of this study can be concluded that there is an effect of the use of social media on student learning behavior as evidenced by the results of testing the accepted hypothesis are Ha and Ho which is indicated by the value of t = 6.011, which is greater than t table = 2.001. Then the level of influence of the use of social media on student learning behavior is in the high category indicated by the tcount value of 6.011. Based on the results of this study, it can be seen that excessive use of social media has a profound effect on learning behavior at school.